Experienced coaches` attitudes towards science and technology - Liebermann, D. G.; Katz, L.; Sorrentino, R. M. (International Journal of Computer Science in Sport, 2005)
In this study, the attitude of experienced coaches towards technologies and sport sciences was assessed. A questionnaire was used to evaluate three areas: (1) Attitudes towards technology and sport science in coaching, (2) Technology and scientific knowledge in practice, and (3) Perceived importance of technology and science in enhancing sport results. A group of 27 highly experienced coaches completed the questionnaire. The questionnaire consisted of three parts, starting with demographic information, followed by a series of 27 questions with answers on a Likert scale ranging from strongly agree to strongly disagree, and finally, coaches were requested to rank 14 well-defined `coaching goals` from 1 (most important) to 14 (least important). Results showed that top-level coaches rated having a good relationship with the athletes` as a major goal. Overall, members of this group of experienced coaches seem to recognize the general importance of sport sciences, and appear to be positive about the use of sport technologies, but do not necessarily translate these positive attitudes into actual practice within their competitive sport environments, even when they all use information technology for other activities. According to these results, sport science researchers and technology developers need to adapt their strategies. Coaching education should encourage coaches to incorporate technologies as part of their coaching routines. Developing innovative resources and incorporating them in coaching education, as is done in some countries, may be a starting point. However, placing the emphasis on educating successful coaches on the practical use of technology and scientific knowledge is suggested as a short-term goal. This may allow for a more immediate effect on the attitude and practice of less senior coaches that tend to adopt methods and training routines through following the personal example provided by top-level coaches.